Peningkatan Kesadaran Masyrakat Tentang Bahaya Sampah Melalui Pembuatan Papan Edukasi (di RT. 33 RW. 04 Kel. Pematang Gubernur Kota Bengkulu) - Puteri, Pongki Resmala; Syafitri, Delfi Ayu; Putra, Septa Zakaria; Saputra, Oven Handeco; Ilahi, Firman Rama Nur; yanti, Rina Trisna; Suwarni, Suwarni; Handayani, Tita (Jurnal Dehasen Untuk Negeri, 2025)
Waste is something that is simply thrown away, and in many cases, waste causes problems for the environment. The World Bank report shows that the amount of waste in cities around the world is expected to continue to increase by 70% from this year to 2025, from 1.3 billion tons per year to 2.2 billion tons per year (Fitri Amalia ,2021). From the results of a field survey that has been conducted in RT 33 RW 04, Pematang Gubernur Village, Muara Bangkahulu District, Bengkulu City, we found that there is still a lot of waste that is not disposed of in its place, thrown in random places and also scattered everywhere. This is what motivates us, students of KKN-T UNIVED RT 33 RW 04 Kelurahan Pematang Gubernur to provide education to create public awareness not to litter. The purpose of installing this waste education sign is to provide awareness to the public about the dangers of littering. The waste sign itself is to explain how long it takes for waste to decompose. The methods used are presentation and consultation. The results of this activity aim to increase public awareness of the dangers of littering and improve the welfare of the people of RT 33 RW 04 Kelurahan Pematang Gubernur (cindy purba,2023).